Throwing a light on oral narrative data in order to inform language and literacy research - Kelleher, William; Masenge, Andries (Journal for Language Teaching, 2022)
Narrative methodologies are valuable to language and literacy research. Oral narratives told in situations of face-to-face interaction are used in research methodologies and in scaffolding pedagogic activities. Nevertheless oral narratives often present limiting cases in which narrative accounts are less easily distinguishable from other genres such as interrogative, expository, descriptive or argumentative accounts. The resulting confusion around genre has an impact on data selection and weighing and thereby on how narrative is mobilised in research and in pedagogic situations. This paper presents the results of a corpus-based statistical investigation into the interactional features of oral narrative accounts collected during academic literacy interviews. Common claims made about narratives, such as that they are structurally differentiated, that they rely on more turns at talk or that they are a unique manner of presenting discrete experiences are not supported in a straightforward way in the corpus data. Narratives do promote more involvement, self-reference, complex embeddings and constructed dialogue. Conversely they are less frequent, less on task and are more consistently aligned with their context. In language and literacy research these findings suggest a need to reflect on the relationship between types of participant response, types of solicitation and allocated response times. The study contributes to differentiating discourse types more accurately and emphasises the particularities of oral narrative interaction.